The utilization of primary health care services and health information needs among adolescents - Siti Khadijah, Ahmad Tajuddin (Universiti Malaysia Sarawak, (UNIMAS), 2009)
it was acknowledged from national survey across the general population that adolescents were the lowest users of health care services. Furthermore, adolescents were the most difficult group to be convinced towards improving their health. The main objectives of the study were to identify adolescents' use of existing government primary health care services in urban and rural settings in Kuching, Sarawak and to identify their health information nee~ This study has identified the large difference between the utilization of government primary health care service between urban and rural settings. The results also indicate that rural adolescents received less care from health professionals and have more frequent visits to health clinics. Yet, they were more than satisfied with the services that were provided to them. In addition, female respondents in urban areas have more clinic visits than male adolescents. On the contrary, more male respondents in rural areas seemed to have frequent clinic visits than female. However, no significant association was found between ,gender and frequency of visits to government primary health care service. In terms of health information, issues involving sexual health and high risk behaviour were unfavourable among the adolescents. Mass media was the main source of information and also, a preferred choice ofaccessing hea1th related issues. These findings would be useful in planning health care services and health promoting programmes targeting the adolescents especially in our primary health care facilities.